Tecnologias para avaliação de ponto de colheita para citricultura e mecanismo para proteção intelectual - Serafin, Cleber Fernando (2021)
The fruit market has been growing in recent years mainly due to the increase in the population's purchasing power, the interest in less processed foods and also the increase in life expectancy, which drives the consumption of healthier foods. The importance of proper determination of the harvest point and evaluation of post-harvest quality in the fruit sector has grown a lot, whether due to the perception of loss reduction, cost reduction and also in the maintenance of product quality. There is also a demand for attributing quality grades to the oranges used to differentiate product prices. The objective of this work was to develop a technological package consisting of low cost colorimetric fruit reading equipment, long-distance wireless data transmission, temperature and relative humidity sensors for operating range under field conditions and conversion program of primary data in conclusive through Arduino processor for the evaluation of pre and post-harvest and prediction of the quality of oranges. This technological package was evaluated by measuring the orange ripeness and its correlation with the evolution of the peel color with the amount of soluble sugars, titratable acidity and pH. The prediction of the color of the fruit was used to verify the prototype's efficiency, after an inventiveness evaluation through the search for the antecedence of equipment patented in Brazil by free search systems with terms in both Portuguese and English. Three intellectual protections were evaluated at INPI and 8 at Google Patents, which after analysis were discarded the hypothesis of being similar, thus indicating the novelty of this prototype. The orange peel color readings from the technological package showed a strong correlation with reference laboratory equipment, indicating a possible industrial use. It also showed a moderate correlation with the concentration of titratable soluble solids, pH and titratable acidity and, therefore, suggests a high potential to increase its TLR (Degree of Technological Maturity) with the possibility of commercial production. It presented a complete degree of technological maturation according to the adapted Mankins methodology (ranging from 1 to 9). The construction cost of the technology package was approximately 20 times cheaper than the reference equipment for use in a controlled environment. All the mandatory documentation necessary for the registration of the prototype's intellectual protection: title, descriptive report, claim table, drawings and abstract were produced. The developed computer program was produced exclusively to transform RGB values (primary data) into orange maturation results, and because it is sui generis, the Hash code was extracted because it presented potential for intellectual protection.